If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(y-10)=3(2y+4)
We move all terms to the left:
-2(y-10)-(3(2y+4))=0
We multiply parentheses
-2y-(3(2y+4))+20=0
We calculate terms in parentheses: -(3(2y+4)), so:We get rid of parentheses
3(2y+4)
We multiply parentheses
6y+12
Back to the equation:
-(6y+12)
-2y-6y-12+20=0
We add all the numbers together, and all the variables
-8y+8=0
We move all terms containing y to the left, all other terms to the right
-8y=-8
y=-8/-8
y=1
| -6(-5y+1)=54 | | 5x+.5x=56 | | 30+9x=43 | | 5x+.5=56 | | 1/3(6x+15)=2x+5 | | 10-x/2=27 | | y+6.25=9.93 | | 5y-3y+4=2y+2y-5 | | 3x-2=27x+4 | | 45k+3=10 | | 4/7x+12=20 | | 3x−1+x=10+x+4 | | 41.10=9g+3.84 | | 3x+2x+10=20 | | -7+2t=-5t | | 5x+14=16x-2 | | 2(x+13)=3x+2+11x | | 5g=9+6g | | 2(2x+7)=230 | | 6x+11=-(6x=5) | | 9m-8m+26m=54 | | -21a+(-60)=66 | | 6n+4n-n+5=2 | | Y=7x-16Y=2(2X-5) | | 13w=30+8w | | 2(t+15)=98 | | 45k+3 =10 | | 27=8x+-4x | | 8x-1.1=9x | | 1/9x+3=15 | | x^2+1/3x=1 | | 36-5w=4w |